2009
DOI: 10.1211/jpp.61.10.0016
|View full text |Cite
|
Sign up to set email alerts
|

Potential beneficial effect of naringenin on lipid peroxidation and antioxidant status in rats with ethanol-induced hepatotoxicity

Abstract: Taken together these findings suggest that naringenin has a therapeutic potential in the abatement of ethanol-induced hepatotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 51 publications
(51 reference statements)
1
20
0
1
Order By: Relevance
“…On the other hand, BREE (125 and 250 mg/kg bw) treated groups significantly (P≤0.05) alleviate the TBA, SOD, GSH and F2-isoprostanes to near normal levels (Table 4). This decrease could be due to ROS inefficient scavenging which might be implicated to oxidative inactivation of enzymes (Jayaraman et al, 2009), which proves to be a potent antioxidant, a finding that correlates with recent reports Arulmozhi et al, 2012;Hsieh et al, 2008). Furthermore, the antioxidant property and the oxygen-radical scavenger of the extract may therefore be due to the presence of polyphenolic high content compounds such as anthocyanins and flavonoids (Mira et al, 2009;Yawadio et al, 2007;Zhang et al, 2010).…”
Section: Effect Of Bree On Tba Sod Gsh and F2-isoprostanes Activitisupporting
confidence: 68%
“…On the other hand, BREE (125 and 250 mg/kg bw) treated groups significantly (P≤0.05) alleviate the TBA, SOD, GSH and F2-isoprostanes to near normal levels (Table 4). This decrease could be due to ROS inefficient scavenging which might be implicated to oxidative inactivation of enzymes (Jayaraman et al, 2009), which proves to be a potent antioxidant, a finding that correlates with recent reports Arulmozhi et al, 2012;Hsieh et al, 2008). Furthermore, the antioxidant property and the oxygen-radical scavenger of the extract may therefore be due to the presence of polyphenolic high content compounds such as anthocyanins and flavonoids (Mira et al, 2009;Yawadio et al, 2007;Zhang et al, 2010).…”
Section: Effect Of Bree On Tba Sod Gsh and F2-isoprostanes Activitisupporting
confidence: 68%
“…NAR was able to prevent LPO due to its molecular structure; perhaps its hydroxyl groups facilitate its adherence to lipid bilayer polar groups, and its nonpolar nucleus may interact with hydrophobic tails of phospholipids, thereby reducing the deleterious effects of free radicals on membranes[12,42,43]. …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that naringenin exhibits various pharmacological effects, including anti-tumor, anti-mutagenic and anti-atherosclerotic effects (17)(18)(19). Studies have suggested that naringenin may reverse the liver damage caused by drugs or toxic chemical compounds, including alcohol, cadmium, carbon tetrachloride, oxytetracycline and dimethyl nitrosamine (20)(21)(22)(23). The present study aimed to investigate the effects of naringenin on DACD.…”
Section: Introductionmentioning
confidence: 96%